Análisis de perfiles de voltaje y pérdidas técnicas empleando curvas de carga, en el Ramal Totoras, Pelileo y Baños a nivel de subtransmisión (69kv) de la empresa eléctrica Ambato S.A. - Barrionuevo Mayorga, Dario Javier (2017)
This research project contains an analysis of the system of subtransmission Totoras Pelileo and Baños to a voltage level of 69 kV, belonging to the Electricity Company Ambato S.A, in order to calculate the losses and voltage level that are presented in the lines and transformers on the basis of the measurements recorded in meters installed in each line output and transformer bars . Through the CYMDIST analysis of flowd to maximum demand with the purpose of obtaining the maximum losses. With the maximum losses obtained from load flows determined voltaje profiles, loss of energy and power that is present in the system,noting of operationally presents critical parts and identifying substations that are impaired voltage in trouble. checking so that the values of the voltage drops are within the regulations issued by the Agency for the Regulation and Control of Electricity (ARCONEL).